Edge-Aware Pyramidal Deformable Network for Unsupervised Registration of Brain MR Images - Cao, Yiqin; Zhu, Zhenyu; Rao, Yi; Qin, Chenchen; Lin, Di; Dou, Qi; Ni, Dong; Wang, Yi (Frontiers in Neuroscience, 2021)
Deformable image registration is of essential important for clinical diagnosis, treatment planning and surgical navigation. However, most existing registration solutions require separate rigid alignment before deformable registration, and may not well handle the large deformation circumstances. We propose a novel edge-aware pyramidal deformable network (referred as EPReg) for unsupervised volumetric registration. Specifically, we propose to fully exploit the useful complementary information from the multi-level feature pyramids to predict multi-scale displacement fields. Such coarse-to-fine estimation facilitates the progressive refinement of the predicted registration field, which enables our network to handle large deformations between volumetric data. In addition, we integrate edge information with the original images as dual-inputs, which enhances the texture structures of image content, to impel the proposed network pay extra attention to the edge-aware information for structure alignment. The efficacy of our EPReg was extensively evaluated on three public brain MRI datasets including Mindboggle101, LPBA40, and IXI30. Experiments demonstrate our EPReg consistently outperformed several cutting-edge methods with respect to the metrics of Dice index (DSC), Hausdorff distance (HD) and average symmetric surface distance (ASSD). The proposed EPReg is a general solution for the problem of deformable volumetric registration.